Public Broadcasting Archives and Academic Use in Germany. Scopes of the Portal for Broadcast Search ‘rufus’ - Patricia F. Blume (VIEW Journal of European Television History and Culture)
This article situates the new online database rufus Rundfunksuche in the German PSB archive landscape. rufus grants researchers in communication and media studies access to the metadata of the ZDF production archive. The text lays out the genesis and framework of the infrastructure as well as its functionality and particular challenges. It explains strategies of data transfer from the archival structure of ZDF to a freely accessible platform for academic use with complex search and filter functions. As a context, the analysis also considers initiatives of other broadcasters implementing less complex search functionalities while working with curatorial strategies. Overall, the article underlines the dynamising effect of the pioneering project on the process of opening up the archives of public broadcasters in Germany.